Bifurcating spatial patterns in a cell-chemotaxis model - Maini, P; Winters, K; Myerscough, M; Murray, J (Wuerz Publishing Ltd, 1993)
Spatial pattern formation is a key issue in early embroynic development. Embroynic cells divide, migrate, and differentiate to form the various structures, markings and organs of the body. Perhaps the most spectacular manifestation of this process is animal coat markings. These patterns are formed by melanin-secreting cells which migrate from the neural crest to the epidermal and dermal layers of the skin.